2013
DOI: 10.1159/000351376
|View full text |Cite
|
Sign up to set email alerts
|

Oral Supplementation of Specific Collagen Peptides Has Beneficial Effects on Human Skin Physiology: A Double-Blind, Placebo-Controlled Study

Abstract: Various dietary supplements are claimed to have cutaneous anti-aging properties; however, there are a limited number of research studies supporting these claims. The objective of this research was to study the effectiveness of collagen hydrolysate (CH) composed of specific collagen peptides on skin biophysical parameters related to cutaneous aging. In this double-blind, placebo-controlled trial, 69 women aged 35-55 years were randomized to receive 2.5 g or 5.0 g of CH or placebo once daily for 8 weeks, with 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
147
2
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(185 citation statements)
references
References 84 publications
(50 reference statements)
8
147
2
10
Order By: Relevance
“…4) Oral treatment with CP and/or gelatin also increases the type I collagen expression in the bones and skin. [5][6][7] Notably, Sato and colleagues identified that CP ingestion increases collagen oligopeptides (COPs) composed of two or three amino acids, including Ala-Hyp-Gly, Pro-Hyp, Pro-Hyp-Gly, Ile-Hyp, LeuHyp, and Phe-Hyp, in human blood, 8,9) suggesting that ingested CP is at least, in part, digested and absorbed as COP.…”
mentioning
confidence: 99%
“…4) Oral treatment with CP and/or gelatin also increases the type I collagen expression in the bones and skin. [5][6][7] Notably, Sato and colleagues identified that CP ingestion increases collagen oligopeptides (COPs) composed of two or three amino acids, including Ala-Hyp-Gly, Pro-Hyp, Pro-Hyp-Gly, Ile-Hyp, LeuHyp, and Phe-Hyp, in human blood, 8,9) suggesting that ingested CP is at least, in part, digested and absorbed as COP.…”
mentioning
confidence: 99%
“…35,36 In a study by Proksch et al, oral supplementation of collagen hydrolysate composed of specific collagen peptides (2.5 g/d or 5.0 g/d for 8 weeks) increased skin elasticity in middle-aged women after 4 weeks of supplementation. 37 Previous studies confirmed that collagen hydrolysate is degraded to small peptides by the gastrointestinal tract, that appear later in the blood stream and reach the skin in 8 up to 96 hours. 38 These peptides are chemotactic for dermal fibroblasts, 39 and promote the migration and growth of mouse skin fibroblasts.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, there is extensive literature showing the benefits of hydrolyzed collagen-based nutraceutical supplements on human skin [21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%